2015
DOI: 10.1007/s13224-015-0672-2
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary Fistula: An Indian Perspective

Abstract: Background In developing countries, obstetric trauma is the most common cause of genitourinary fistulae. But over the last two decades, health care facilities have been improved and the scenario has been changed. Purpose The aim of the present study is to share our experience with genitourinary fistula in terms of mode of presentation, diagnostic modality, and management with the emphasis on the surgical approach and a parallel review of the available literature. Materials and Method During a 6-year period fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
2
6
1
Order By: Relevance
“…The average age in both study groups was 26±8.02 years, similar to reports from Africa and Asia with the mean age at treatment around 25-29. [22][23][24] Proportion of unmarried women (65.2%) was higher than that of 40 to 50 % reported by others. 25,26 The majority of patients in both study populations had primary level of education (54.3%).…”
Section: Discussionmentioning
confidence: 55%
“…The average age in both study groups was 26±8.02 years, similar to reports from Africa and Asia with the mean age at treatment around 25-29. [22][23][24] Proportion of unmarried women (65.2%) was higher than that of 40 to 50 % reported by others. 25,26 The majority of patients in both study populations had primary level of education (54.3%).…”
Section: Discussionmentioning
confidence: 55%
“…A study from Ethiopia (2011–2015) reported that among 2500 fistula cases, 24.6% were attributed to surgical cause, particularly cesarean delivery and hysterectomy . An Indian study conducted from 2007 to 2013 reported that 39% of genitourinary fistulae were iatrogenic . A further study, conducted from 2011 to 2015 in India, reported that 65% of fistula cases were iatrogenic .…”
Section: Discussionmentioning
confidence: 99%
“…Obstructed labor is the main cause of VVF in the rural areas accounting for between 56 and 97.88% in some series [4,[12][13][14][15][16].…”
Section: Causes Of Genitourinary Fistulasmentioning
confidence: 99%
“…The surgical residents at the Federal Medical Center Owerri, Nigeria perform circumcision under the supervision of team consultants since 2000. The less commonly occurring vesicouterine fistula (VUF) and vesicocervical fistula are complications of difficult cesarean sections (CS) [16], and uterine rupture. When urinary fistula occurs as a complication of treatment the effect is devastating to the trained care giver even though the propensity for medicolegal litigation is very low in the rural areas.…”
Section: Causes Of Genitourinary Fistulasmentioning
confidence: 99%
See 1 more Smart Citation